An Abnormal Origin and Branching Pattern of the Right Subscapular Artery: A Case Report School of Basic Medical Sciences, Faculty of Medicine, Universiti Sultan Zainal Abidin, Terengganu, Malaysia. - Lakshmi, Annamalai; Norhazilah, Muhamad; Yasrul Izad, Abu Bakar; Asma', Hassan; Fatimah Murniwati, Tg. Muda (2016)
The use of upper limb vascular channels for diagnostic and interventional procedures makes it important for us to report any abnormalities in their course and branching patterns. During routine dissection of an embalmed male cadaver, an unusual origin and branching pattern of the right subscapular artery was observed. The subscapular artery originated much higher up, from the second part of the right axillary artery, close to the origin of the lateral thoracic artery. Apart from the circumflex scapular artery and the thoracodorsal artery, the subscapular artery also gave a few branches to the lateral thoracic wall. Close to its origin the subscapular artery was wound around by the medial pectoral nerve. The origin and branching pattern of the subscapular artery on the left side was found to be normal. As the subscapular artery is the largest branch of the axillary artery such findings must be kept in mind during surgeries of the axilla, mastectomy and infraclavicular brachia! plexus block to prevent profuse bleeding during these procedures.